Controlled experiments on dissolution and remediation of 2,4,6-trinitrotoluene in distilled water and seawater - Sadler, Joseph; Movshovitz, Matar; Persico, Federica; Mai, Nathalie; Fernandez Lopez, Carmen; Şen, Nilgün; Humphreys, Lisa; Kadansky, Evie; Webb, Sally; Sharma, Bhumika; Wardrop, Joshua; Coulon, Frederic; et al. (Elsevier, 2026)
Prior to the ratification of the London Convention on the Prevention of Marine Pollution by Dumping of Wastes and Other Matter in 1972, dumping of military munitions at sea was considered a safe and secure method of disposal. There is increasing desire to remove the now corroding and unstable munitions from this prime ocean real estate to develop offshore wind and solar farms. However, after 50–100 years of exposure to the marine environment, corroded munitions may be leaching toxic explosives to the environment, and remediation methods involving detonation are also likely to leave toxic residue. Therefore, to investigate the potential for explosive leaching at dump sites, the dissolution of the common high explosive 2,4,6-trinitrotoluene (TNT) in seawater was investigated. Then, to determine the potential for remediation, the efficacy of commercial activated carbon and waste derived biochar for adsorption of TNT from seawater was investigated. It was observed that TNT dissolves slower in seawater compared to distilled water, which suggests that explosives in underwater ordnance may remain in bulk mass for longer periods of time than expected and be easier to remove. Furthermore, the small-scale laboratory test demonstrated that both activated carbon and biochar reduced the concentration of TNT in distilled and seawater by up to 90 % after only 2 h. This study provided insight into alternative sustainable remediation options for TNT-contaminated water using commercially available activated carbon and biochar generated from waste products.
Keywords: 41 Environmental Sciences; 4104 Environmental Management; 14 Life Below Water; Activated carbon; Biochar; Contaminated seawater; Explosives; Unexploded ordnance; Adsorption